1977
DOI: 10.1111/j.1469-8986.1977.tb03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate as a Discriminative Stimulus

Abstract: Two experiments were performed to evaluate characteristics of heart activity as discriminative stimuli. In Study I two multiple baseline across subjects designs were utilized to assess the efficacy of trial and error and fading procedures in increasing the detection of heart rate activity above and below an average level. Both trial and error and fading procedures were effective in increasing discrimination accuracy. A 4.4 bpm interval around the subject's mean heart rate was employed as the discriminative sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The results of the present study are consistent with previous research in which physiological cues are established as discriminative stimuli (e.g., Brener and Jones, 1974;Epstein and Stein, 1974;Epstein, Cinciripini, McCoy, and Marshall, 1977). An interesting finding was the maintenance of feedback effects in Group I for two weeks following feedback withdrawal.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are consistent with previous research in which physiological cues are established as discriminative stimuli (e.g., Brener and Jones, 1974;Epstein and Stein, 1974;Epstein, Cinciripini, McCoy, and Marshall, 1977). An interesting finding was the maintenance of feedback effects in Group I for two weeks following feedback withdrawal.…”
Section: Discussionsupporting
confidence: 92%
“…Heart rate is probably the parameter that has been most frequently used, probably because palpitation is often reported by phobic clients and because it is rather easily measured in the laboratory and in in vivo situations. The interoceptive discrimination of changes in heart rate has, however, been reported to be rather low in normal, resting situations (Brener and Jones, 1974;Epstein et aL, 1977;Epstein and Stein, 1974;Clemens, 1979). Borkovec (1976) has described a self-rating scale originally developed by called the Autonomic Perception Questionnaire (APQ) where the client is to rate to what extent he/she perceives changes in different physiological parameters when feeling anxious.…”
Section: Introductionmentioning
confidence: 98%
“…The results of all three studies suggested that perfor-mance feedback facilitated cardiac perception. However, as Ashton et al (1979) and Epstein et al (1977) have pointed out, these studies were not designed to indicate which sensory events are actually being perceived or what particular strategies were being utilized. Thus, a major purpose of the fIrst of two experiments described below was to identify which cues, of those available in external feedback, were utilized by subjects to improve cardiac perception.…”
mentioning
confidence: 99%